IoT-Enabled Remote Monitoring Techniques for Healthcare Applications -- An Overview (Informatica, 2022)
IoT-enabled remote healthcare monitoring applications have surged against countless other technologies to assist patients. Recently, the healthcare sector has sought a devastating escalation in augmenting appropriate monitoring technologies for effective remote monitoring and improved diagnostics during the pandemic era -- i.e., the existing methods need to be revamped with sophisticated technologies. In this paper, remote monitoring techniques proposed for healthcare applications and their challenges are surveyed. In addition, a healthcare architecture for effective remote monitoring is explored. It was observed that most of the solutions focused on the application of edge analytics and deep learning mechanisms. The review aimed at guiding healthcare practitioners and developers to understand the pitfalls of existing approaches and to innovate solutions in newer dimensions.